Деякі аспекти взаємовпливу давньоруської та сіверянської гончарних традицій - Сорокін, С.О.; Ситий, Ю.М. (Археологія, 2022)
У статті розглянуто знахідки роменської кераміки, що імітували давньоруський гончарний посуд.
Проаналізовано передумови для його появи й теорії дослідників щодо існування такого посуду й часу
його появи. The article considers the issues of mutual influence of two pottery traditions in the production of tableware — the Ancient Rus
and Romny cultures in the 10th — first half of the 11th centuries. Various theories of scientists dealing with this issue are analyzed
and new materials of research of archaeological complexes in Sedniv and Liubech in Chernihiv Oblast are put into scientific
circulation. The traditions of pottery are the most conservative during the existence of archaeological cultures. Technological
techniques, vessel shapes, types of impurities, firing methods, surface ornamentation appear at its beginning and do not change.
Radical changes occur only in the case of a certain external influence, and the massive one. Occupation of the Left Bank of the
Dnipro River and, in particular, the Desna River region by the bearers of the Ancient Rus culture during the 10th century was
such a factor. The technological traditions brought with them were adapted to local realities in different ways. The process of
interaction between the two pottery traditions took place on different territories at different times — during the strengthening of
the Rus influence on the Severians. The expansion of the borders of Rus led to the emergence of the Ancient Rus pottery among
the Severians, and this led to experiments in the manufacture of the Romny culture utensils similar in shape and ornamentation to
the Ancient Rus products. There appeared pots made of traditional for the Romny culture molding masses decorated with linear
and wavy ornaments with a profiling on top similar to the ancient Rus items. Such experiments did not last long and over time
wheel-made ceramic ware completely replaced the traditional handmade one.